Caracterização do trânsito de bovinos nos estados do Paraná e Santa Catarina, Brasil, 2008 - Paula Luiza Silveira de Felipe (2010)
The international trade rules and the requirements of commercial partners of Brazil in the beef market makes animal defense organisms provide greater accuracy in control of their health products. This work aims to inform research institutions and market chain meat through amethodology of an epidemiological study based on GIS, which aims to characterize the movement of cattle in the States of Parana and Santa Catarina in 2008. The need for the state of Parana become free without vaccination and the state of Santa Catarina maintain their free status without vaccination for FMD, and thereby both increase the area of performance in the export of meat products, demonstrates the importance of knowledge of these regions to encourage programs of prevention, control and eradication of disease in general. The characterization of the geographic areas was divided into three stages: descriptive analysis, spatial analysis and networking flow analysis. These studies were generated through a database provided by the Ministry of Agriculture, Livestock and Supply. The State of Paranáshowed some regionalization of flow between the regions of bovine origin and the poles of slaughter, both focused on the north and northwest. The State of Santa Catarina has been focused its slaughter poles in east and southbound, but animals origin are from different regions of the State. The methodology of this study intends to contribute as an exploratory toolfor implementation of strategic actions in systems of surveillance.